중저준위방사성폐기물 처분시설의 처분농도제한치 설정에 대한 고찰 II: 최적화 방법론 개발 및 적용 - 홍성욱(Sung-Wook Hong), 김민성(Minseong Kim), 정강일(KangIl Jung), 박진백(Jin Beak Park) (Journal of nuclear fuel cycle and waste technology (Online), 2017)
2014년 12월 사용 승인된 경주 중저준위 방사성폐기물 동굴처분시설은 중저준위 방사성폐기물의 처분을 위해 운영중이나 중준위 방사성폐기물을 처분할 수 없다. 왜나하면 기존 중준위 방사성폐기물이 원자력안전위원회 고시 2014-003호에 따라 방사성폐기물 준위가 세분화되었으며, 기존의 중저준위 방사성폐기물 핵종별 처분농도제한치 값이 변경되었으나 이를 고려 하지 못하였기 때문이다. 중준위 방사성폐기물의 안전한 처분을 위해 IAEA에서 제시한 방법론과는 달리 방사능량 산출 시 적용된 가용데이터를 기반으로 기존의 설정된 극저준위 및 저준위 방사성폐기물의 처분농도제한치를 고려하여 1단계 동굴 처분시설의 중준위 방사성폐기물에 대한 처분농도제한치를 설정하였다. 단, 14C의 경우 처분농도제한치 외에 추가적인 방사 능량 제한이 필요함을 확인하고 우물이용시나리오를 통해 1단계 동굴처분시설의 총방사능량을 제한하였다. 설정된 중준위 방사성폐기물 처분농도제한치와 14C의 총방사능량이 적용된 방사능량에 대해 운영 중 및 폐쇄 후 시나리오의 평가결과가 모 두 성능목표치를 만족함을 확인하여, 도출된 중준위 방사성폐기물 처분농도제한치가 1단계 동굴처분시설의 중준위 방사성 폐기물 처분농도제한치로 사용할 수 있음을 확인하였다. 처분 안전성 증진을 위해 방사성폐기물 발생기관의 데이터를 추가 확보하며, 14C의 누적방사능량을 관리해 나갈 계획이다. The Gyeongju underground silo type disposal facility, approved for use in December 2014, is in operation for the disposal of low and very low-level radioactive wastes, excluding intermediate-level waste. That is why the existing low-level radioactive waste level has been subdivided and the concentration limit value for intermediate-level waste has been changed in accordance with Nuclear Safety Commission Notice 2014-003. For the safe disposal of intermediate-level wastes, new optimization methodology for calculating the concentration limit of intermediate radioactive level wastes at an underground silo type disposal facility was developed. According to the developed optimization methodology, concentration limits of intermediate-level wastes were derived and the inventory of radioactive nuclides was evaluated. The operation and post closure scenarios were evaluated for the derived radioactive nuclide inventory and the results of all scenarios were confirmed to meet the regulatory limit. However, in case of 14C, it was confirmed that additional radioactivity limitation through a well scenario was needed in addition to the limit of disposal concentration. It was confirmed that the derived intermediate concentration limit of radioactive waste can be used as the intermediate-level waste concentration limit for the underground disposal facility. For the safe disposal of intermediate-level wastes, KORAD plans to acquire additional data from the radioactive waste generator and manage the cumulative radioactivity of 14C.